Papular lesion occurring within a longstanding warty plaque, in skin of colour Fitzpatrick type 4-5 - Joelle Teoh; Alex Gan; Joshua Ramalingam; Somaia Elsheikh; Richard Jerrom (Wiley, 2024)
Abstract A 23‐year‐old man of South Asian descent, Fitzpatrick type 4-5 skin, usually fit and well, presented with a 6‐month history of a darkly‐pigmented papular lesion growing within a pre‐existing warty plaque on the left parietal scalp, present since birth. The base plaque measured 30 × 10 mm, whilst the new papule measured approximately 3 × 3 mm. These were asymptomatic and there was no preceding trauma to the area. Examination revealed a pearlescent darkly pigmented papule, growing within a warty pink‐yellow hairless plaque. Dermoscopy showed non‐specific features with evidence of some disorganized vasculature. A punch excisional biopsy of the papular lesion was obtained, histopathology indicated a polypoid lesion with basaloid nests in a superficial and nodular distribution extending to the superficial dermis. The base plaque was then completely excised, showing dermal scarring related to the previous excision, along with the presence of large sebaceous glands, heterotopic apocrine glands, defective hair follicles, acanthosis and epithelial papillomatosis. This is a case of a basal cell carcinoma (BCC) arising within a sebaceous naevus on the scalp, in a skin of colour patient. Sebaceous naevi (SN), also known as naevus sebaceous of Jadassohn, are benign hamartomatous malformations comprised of predominantly sebaceous glands. SN appear most commonly on the scalp, and start off as smooth yellowish well‐circumscribed plaques in infancy which then develops a verrucous appearance in adolescence due to hormonally‐driven maturation of sebaceous and apocrine glands. It is well known that benign neoplasms of various lineages of differentiation including follicular, sebaceous, apocrine or eccrine, may arise within SN. Malignant neoplasms occurring within SN almost exclusively occur in adults, and arise in about 2.5% of lesions. BCCs are the most common among these, and occur in 0.8% of SN. Other malignant tumours such as squamous cell carcinoma, sebaceous carcinoma, microcystic adnexal carcinoma and porocarcinoma can also arise within SN, but these are rarer. Our case is notable as our patient had Fitzpatrick skin type 4-5, hence may have been perceived to have a lower risk of developing BCCs. We hope that this report will highlight that BCCs do arise even in skin of colour.